Design, Control, and Experimentation of Internally‐Actuated Rovers for the Exploration of Low‐gravity Planetary Bodies. Issue 1 (20th June 2016) - Hockman, Benjamin J.; Frick, Andreas; Reid, Robert G.; Nesnas, Issa A.D.; Pavone, Marco
Abstract : This paper discusses the design, control, and experimentation of internally‐actuated rovers for the exploration of low‐gravity (micro‐g to milli‐g) planetary bodies, such as asteroids, comets, or small moons. The rover is actuated by spinning three internal flywheels, which allows all subsystems to be packaged in one sealed enclosure and enables the platform to be minimalistic, thereby reducing its cost. By controlling the spin rate of the flywheels, the rover can achieve large surface coverage by attitude‐controlled hops, fine mobility by tumbling, and coarse instrument pointing by changing the orientation relative to the ground. We first discuss the dynamics of such rovers, their control, and key design features (e.g., flywheel shape and orientation, geometry of external spikes, and system engineering aspects). We then discuss the design and control of a first‐of‐a‐kind test bed that enables the accurate emulation of a microgravity environment for mobility experiments, which consists of a three‐degree‐of‐freedom gimbal attached to an actively controlled gantry crane. Finally, we present experimental results on the test bed that provide key insights for rover control and validate our theoretical analysis.